The role and mechanism of Asian medicinal plants in treating skin pigmentary disorders - Li, Yumeng; Huang, Jinhua; Lu, Jianyun; Ding, Yufang; Jiang, Ling; Hu, Shuanghai; Chen, Jing; Zeng, Qinghai (Journal of ethnopharmacology, 2019)
Chloasma, senile plaques, vitiligo and other pigmentary disorders seriously affect patients’ appearance and life quality. Medicinal plant is the product of long-term medical practice worldwide, with the advantages of outstanding curative properties and less side effects. Recently, research were made to explore the value of medicinal plants in the treatment of pigmentary disorders, and remarkable results were achieved. This review outlines the current understanding of the role and potential mechanisms of medicinal plants (including active ingredients, extracts and prescriptions) in pigmentary disorders, especially Chinese medicinal plants, provides the preclinical evidence for the clinical benefits. This study hopes to provide comprehensive information and reliable basis for exploring new therapeutic strategies of plant drugs in the treatment of skin pigmented diseases. The literature information was obtained from the scientific databases (up to Oct, 2017), mainly from the PubMed, Web of Science and CNKI databases, and was to identify the experimental studies on the regulating melanogenesis role of the active agents from herbal medicine and the involved mechanisms. The search keywords for such work included: “pigmentary” or “pigmentation”, “melanogenesis”, and “traditional Chinese medicine” or “Chinese herbal medicine”, “herb”, “medicinal plant”. We summarized the function of medicinal plants involved in melanogenesis, especially Chinese medicine. It was reported that the active ingredients, extracts, or prescriptions of medicinal plants can regulate the expression of genes related to melanogenesis by affecting the signaling pathways such as MAPK and PKA, thereby regulating pigment synthesis. Some of them can promote melanogenesis (such as isoliquiritigenin, geniposide; Cornus officinalis Siebold & Zucc., Eclipta prostrata (L.) L.; the Bairesi complex prescription, etc.). While others have the opposite effect (such as biochanin A, Gomisin N; Panax ginseng C.A. Meyer, Nardostachys chinensis Bat.; Sanbaitang, etc.). Asian medicinal plants, especially their active ingredients, have multilevel effects on melanogenesis by regulating melanogenesis-related genes or signaling pathways. They are of great clinical value for the treatment of skin pigmentary disorders. However, the experimental effect, safety, and functional mechanism of the medicinal plants require further determination before studying their clinical efficacy. [Display omitted]